Facile synthesis of carbon-doped graphitic C3N4@MnO2 with enhanced electrochemical performance. Issue 86 (2nd September 2016) - Shan, Qian Yuan; Guan, Bo; Zhu, Shi Jin; Zhang, Hai Jun; Zhang, Yu Xin
Abstract : Exploiting the synergistic advantages of two dimensional architectures, carbon-doped graphitic carbon nitride (CCN) and MnO2 were coupled to design a highly efficient carbon-doped graphitic carbon nitride@MnO2 (CCNM) composite for supercapacitors. Abstract : Exploiting the synergistic advantages of two dimensional-two dimensional architectures, carbon-doped graphitic carbon nitride (CCN) and birnessite manganese oxides (MnO2 ) were coupled to design a highly efficient novel carbon-doped graphitic carbon nitride@MnO2 (CCNM) composite for supercapacitors via a facile hydrothermal method. The structural, morphological and electrochemical properties of the composite were characterized by various physicochemical techniques. These findings indicate that the existence of carbon doping can improve the rate performance of composite electrodes. The specific capacitance in a three-electrode system was 324 F g −1 at a current density of 0.2 A g −1 with capacitance retention of 80.2% after 1000 cycles. In principle, the supercapacitor performance was correlated with the hierarchical structure of the CCNM.